Identification of nonalcoholic fatty liver disease following pancreatectomy for noninvasive intraductal papillary mucinous neoplasm. (October 2018) - Luu, Carrie; Thapa, Ram; Rose, Trevor; Woo, Katherine; Jeong, Daniel; Thomas, Kerry; Chen, Dung-Tsa; Friedman, Mark; Malafa, Mokenge P.; Hodul, Pamela J.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) following pancreatectomy is a potential cause of long term morbidity in patients undergoing pancreatic resection with curative intent. Prior studies have reported an incidence of NAFLD up to 30% following pancreatectomy but the investigated cohorts were typically a mix of benign and malignant disease. Here we examined the incidence of NAFLD in a homogenous cohort of patients following pancreatectomy for benign intraductal papillary mucinous neoplasm (IPMN). Methods: A retrospective review of patients who underwent pancreatic resection for IPMN from 2000 to 2016 was performed. Post pancreatectomy CT/MRI scans were obtained as standard surveillance. We investigated changes in the liver parenchymal density on post surgical imaging to estimate the frequency with which NAFLD occurred. Radiographic criteria for NAFLD included Hounsfield units less than 40 on CT or liver:spleen ratio <0.9 on CT or MRI. Fischer's exact test, Kruskal-Wallis test, and logistic regression were performed. Results: Our study cohort included 109 patients who underwent pancreatectomy for nonmalignant intraductal papillary mucinous neoplasm with no evidence of NAFLD preoperatively and at least 6 months follow-up. Mean follow-up was 52 months (range 8–130/months). The incidence of postoperative NAFLD was 17/109 (15.6%). Most cases occurred within 12 months of pancreatectomy. On multivariate analysis, proximal pancreatectomy (pancreaticoduodenectomy) and development of atrophy of the pancreas remnant were significant risk factors for development of hepatic steatosis (p < 0.05). Conclusion: Patients undergoing pancreatectomy for benign disease have a significant risk of developing NAFLD but the frequency is lower than previously reported in cohorts that included individuals with malignant disease. Highest risk was observed in individuals who underwent pancreaticoduodenectomy or developed pancreatic atrophy. Further investigations to define the mechanisms that promote steatosis and interventions to prevent subsequent morbidity from NAFLD are warranted. Highlights: The rate of NAFLD after pancreatic resection for benign IPMN is low. Pancreaticoduodenectomy and pancreatic remnant atrophy are associated with NAFLD. The incidence of serious sequelae due to NAFLD in this population appears to be low. Longer follow-up may identify additional risk factors for NAFLD and cirrhosis.